UPAYA PENINGKATAN KESELAMATAN LALU LINTAS PADA DAERAH RAWAN KECELAKAAN DITINJAU DARI SEGI PERLENGKAPAN JALAN DAN PERSEPSI PENGGUNA JALAN (JALAN AHMAD YANI MAUMERE KABUPATEN SIKKA) - Kristina D Anggreni; Yono Putra; Alfrendo Satriawan Kabupung (Program Studi Teknik Sipil, 2023)
The number of accidents that occurred on Jalan Ahmad Yani Maumere, Sikka Regency during the last 4 (four) years has often decreased and increased, causing the number of fatalities to increase every year. The condition of traffic flow and speed on the Ahmad Yani road section is quite high due to its function as a secondary collector road and the land use around the road section includes offices, schools, shopping centers causing frequent conflicts and traffic problems, especially in the field of road safety. This research aims to to improve safety in road traffic as well as road users' perceptions of improving road safety. The research was carried out by observing and inventorying the condition of equipment facilities along Jalan Ahmad Yani and the perceptions of road users who filled out questionnaires totaling 30 respondents in order to obtain treatment suggestions based on the results of the analysis. The results of the research show that the high number of accidents on the Ahmad Yani road is largely caused by a lack of awareness of road users and suboptimal road facilities and infrastructure. Therefore, it is necessary to evaluate road safety by conducting routine and periodic inspections.